Predicting Live Body Weight using Morphometric Measurements in Jersey and Holstein Dairy Cows - Shah, Anees Ahmad; Dar, Rameez Ali; Pattoo, Raoof Ahmad; Shah, Syed Mohmad; Yatoo, Manzoor Ahmad (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Live body weight estimation in dairy animals is an important activity with regard to animal performance monitoring. Traditional weighing  bridges/platforms, though accurate are costly for a farmer and have portability issues making them unavailable in field conditions. Present  study was conducted to determine the correlation between live body weight and linear/ morphometric measurements in Jersey and HF  cattle at an organized farm under the temperate climate of Jammu & Kashmir. Five linear body measurements i.e., body length, chest  girth, belly circumference, pelvic girth and withers height were taken at different ages over a period of 3 years wherein a total of 231  recordings from Jersey and 114 from HF cattle pertaining to each of the mentioned parameters were made. The live weights of these  animals were also recorded on the same days using conventional weighing bridges. In Jersey cattle, the highest correlation observed  was with chest girth (+0.89) followed by pelvic girth (+0.80) and withers height (+0.76). Similarly in HF cattle, highest correlation was  observed with chest girth (+0.95) followed by body length (+0.92) and pelvic girth (+0.89). Regression analysis revealed a best-fit equation  for predicting live weight with body length, chest girth and withers height in Jersey (R2= 0.73) and with chest girth and body length  in HF (R2= 0.95) cattle. It was concluded that the correlation between live body weight and linear body measurements can be suitably  exploited to predict live body weight in dairy cattle in the absence of conventional means of live weight estimation.
Keywords: Cattle, Linear measurements, Morphometry, Prediction, Regression